Recurrent breast cysts - Romak, R. P. (Journal of Education, Health and Sport, 2015)
Romak R. P. Recurrent breast cysts. Journal of Education, Health and Sport. 2015;5(7):91-95. ISSN 2391-8306. DOI 10.5281/zenodo.19222 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A91-95 https://pbn.nauka.gov.pl/works/577101 http://dx.doi.org/10.5281/zenodo.19222 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015. Recurrent breast cysts Romak R. P. Odessa National Medical University, Odessa, Ukraine Abstract The purpose of the study to determine the frequency of recurrence of breast cysts. The study was conducted on the basis of Odessa regional clinical hospital (Odessa, Ukraine). Medical records of 300 records of patients treated at the hospital in 2010-2014 were retrospectively analyzed. The analysis of frequency of recurrent cysts as well as the main trends in the choice of methods of diagnosis and treatment was conducted. The average age of patients was 38,3 ± 0,7 years. In order to use diagnostic mammography (33.5%), ultrasound investigation (50.5%), a combination of ultrasound and mammography (16.0%). The diagnosis was confirmed by fine needle aspiration puncture, which is performed under visual control at 20.5%, under ultrasound guidance - in 79.5% of patients. The recurrence rate was 41.5%, in 3.0% of cases have been repeated relapses. Sectoral resection is considered to be a treatment of choice for recurrent breast cysts. Key words: breast cysts, diagnosis, surgery.